UNDERSTANDING LASUNA AS RASAYANA - A CRITICAL REVIEW - Pareek, Tribhuvan; Singh Tiwari, Sandeep; Juneja, Nitin (International Journal of Ayurveda and Pharma Research, 2016)
The Medicinal use of Garlic is not new to the world today. Garlic plays important role in daily diet and also helps in maintaining good health thats why it is widely suggested by physicians. Lasuna is a most potent herb used in many conditions mainly used as a Rasayana in Vatavyadhi, Amavata etc. The essential chemical components of Garlic are helpful in daily routine for making physic fit and it acts over Hypercholesterolemia. The wide range of Garlic, health benefits come mainly from its main ingredient, Allicine. This widely researched component of garlic is highly therapeutic and is used in various drugs and pharmaceutics. Many Acharyas used this potent herb in many formulations like Lashoonadi vati, Lashoona ksheera paka etc. Rejuvenation therapy enhances the energy and the person’s mental and physical capabilities. A number of studies suggest that rejuvenation therapy is effective in improving the skin complexion, texture, in modulating the voice and in increasing the sensing capacity of the sense organs. Rasayana is that which provides optimum quality of the bodily tissues due to which it provides both mental and physical health, prevents ageing and disease, thus enables to live for a longer period of youthfulness. In current article importance of Garlic is shown as Rasyana, as its indication and properties of Garlic as per Ayurveda suggest its work as Rasayana.